The generalized [beta]-method in Taguchi experiments - Joachim Kunert; Frank Lehmkuhl (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 1997)
In the presence of variability control factors in Taguchi experiments, then the original b-method (Logothetis 1990) is liable to lead to wrong transformations. We propose a generalization of the b-method which should lead to correct transformations, even if there is a variability control factor which also influences the mean.
Keywords: 519; Design factor; target control factor; transformation; variability control factor